2013
DOI: 10.1038/ncomms2526
|View full text |Cite
|
Sign up to set email alerts
|

Loss of TRPM2 function protects against irradiation-induced salivary gland dysfunction

Abstract: Xerostomia as a result of salivary gland damage is a permanent and debilitating side effect of radiotherapy for head and neck cancers. Effective treatments for protecting, or restoring, salivary gland function are not available. Here we report that irradiation treatment leads to activation of the calcium-permeable channel, transient potential melastatin-like 2 (TRPM2), via stimulation of poly-ADP-ribose polymerase. Importantly, irradiation induced an irreversible loss of salivary gland fluid secretion in TRPM2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(106 citation statements)
references
References 50 publications
6
100
0
Order By: Relevance
“…As a popular cancer therapeutic approach, radiotherapy kills both cancer cells and bystander normal cells, thereby remarkably affecting the integrity and function of healthy tissues [27]. Recently, wealth of clinical studies support the notion that radiotherapy-mediated side effects remain a conundrum, intertwined with impaired life quality of survivors.…”
Section: Discussionmentioning
confidence: 99%
“…As a popular cancer therapeutic approach, radiotherapy kills both cancer cells and bystander normal cells, thereby remarkably affecting the integrity and function of healthy tissues [27]. Recently, wealth of clinical studies support the notion that radiotherapy-mediated side effects remain a conundrum, intertwined with impaired life quality of survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Although the data presented above demonstrates activation of a nonselective cation current across the plasma membrane and a rise in [Ca 2+ ] cyt in hepatocytes in response to acetaminophen treatment, the identity of the channels responsible for this Ca 2+ entry is not known. One possible candidate that is activated in response to oxidative stress is the TRPM2 (24)(25)(26). Evidence that acetaminophen-induced nonselective cation current is mediated by TRPM2 is as follows: (i) the current shows a linear I-V relationship; (ii) it is blocked by clotrimazole and ACA; and (iii) it is activated by H 2 O 2 (19,27).…”
Section: Acetaminophen-induced Nonselective Cation Current In Hepatocmentioning
confidence: 99%
“…A major drawback in developing a successful treatment strategy for this condition has been the lack of clear understanding of the mechanism by which irradiation (IR) induces a decrease in salivary gland function. The studies in several animal models, including mini-pig, rats and mice, 611 have reported that following a single dose of IR there is a slow loss of salivary gland tissue 3 due to likely damage of progenitor cell population within the gland. 12 In addition, the effects of IR on neuronal cells as well as vasculature have also been suggested to contribute to the loss of salivary gland function and regenerative capacity.…”
Section: Introductionmentioning
confidence: 99%